The effects of environmental factors on rainbow smelt Osmerus mordax embryos and larvae - K. M. Fuda; B. M. Smith; M. P. Lesser; B. J. Legare; H. R. Breig; R. B. Stack; D. L. Berlinsky (Journal of Fish Biology, 2007)
Experiments were conducted to identify environmental factors that influence the survival of rainbow smelt Osmerus mordax during their early life stages. Developing rainbow smelt embryos and yolk‐sac larvae were cultured under controlled conditions with different dissolved oxygen (DO; 1·09, 2·18, 4·37 and 6·55 mg l −1 , pH (4·0, 4·5, 5·0, 5·5, 6·0 and 7·0), nitrate ( 0·7, 3·6, 7·3, 14·6 and 29·2 mg l −1 ), phosphate (0·04, 0·21, 0·42, 2·08 and 4·17 mg l −1 ) and salinity (0, 5, 10, 15, 20 and 30) levels. Rainbow smelt embryos were also incubated with simulated tidal salinity fluctuations (2–28), ultraviolet radiation (irradiances of 2·8, 6·2 and 5·1 W m −2 ) and under natural conditions in two rainbow smelt spawning rivers. In the laboratory, hatch was only impaired under the lowest DO and pH conditions (0 and 13% hatch, respectively) and at highest constant salinity levels (0% hatch). Larval survival was only affected by pH levels ≤5·0. The experiment that compared hatch under natural conditions was terminated when embryos became covered with silt and fungus. These results suggest that water acidification, sediment and fungal growth may affect rainbow smelt survival during their early life stages.